Nitrate Treatment Alters Metabolite Abundance and Fuel Preference in Exercised Zebrafish. (29th May 2020) - Wolfe, Mandy; Beaver, Laura; Keller, Rosa; Hord, Norman
Abstract: Objectives: Nitrate, found abundantly in green leafy vegetables, may improve exercise performance by increasing availability and utilization of metabolic fuels that require less oxygen for energy production. However, it is not known if the performance effect occurs at the peak exercise intensity. We hypothesize that supplemental nitrate treatment will promote the metabolism of specific fuels (carbohydrates versus fatty acids) during exercise that require less oxygen to produce ATP. Metabolic analysis will quantify if a net change in these fuels are linked to an improvement in exercise performance with nitrate treatment during submaximal exercise conditions. Methods: Adult zebrafish were exposed to sodium nitrate (606.9 mg NaNO3 /L water) or control water for 21 days (n = 54). Fish were sampled at three conditions during a graded exercise test: 1) rested, 2) peak speed, and 3) post-exercise. Whole fish tissue was homogenized and analyzed using high-pressure liquid chromatography Triple Q-ToF mass spectrometry based untargeted metabolomics. Results: Metabolomics analysis resulted in the detection of 12, 135 and 10, 604 features in positive and negative ion mode respectively. Preliminary results show succinate levels significantly increased in nitrate-treated rested fish as compared to control rested fish. Likewise, a significant increase in methylmalonate, which serves as a vital intermediate in the catabolism of lipids and protein, was detected in nitrate-treated fish at rest relative to rested controls. Nitrate treatment both at rest and at peak exercise intensity, significantly increased the abundance of various acyl carnitines relative to control fish at the same exercise intensity, and these metabolites function to transfer long-chain fatty acids to mitochondria for β-oxidation, relative to control fish at the same exercise intensity. Work is ongoing to further identify metabolites that significantly changed with nitrate treatment at various exercise intensities. Conclusions: Our data are consistent with the hypothesis that nitrate treatment may alter lipid and carbohydrate metabolism of zebrafish. Funding Sources: Celia Strickland and G. Kenneth Austin III Endowment, the Oregon Agricultural Experimental Station, and National Institutes of Health.